Secrets and Leaks : The Dilemma of State Secrecy - Sagar, Rahul (Book collections on Project MUSE., 2013)
Secrets and Leaks examines the complex relationships among executive power, national security, and secrecy. State secrecy is vital for national security, but it can also be used to conceal wrongdoing. How then can we ensure that this power is used responsibly? Typically, the onus is put on lawmakers and judges, who are expected to oversee the executive. Yet because these actors lack access to the relevant information and the ability to determine the harm likely to be caused by its disclosure, they often defer to the executive's claims about the need for secrecy. As a result, potential abuses are more often exposed by unauthorized disclosures published in the press. But should such disclosures, which violate the law, be condoned? -- Publisher website.